Maternal polycystic ovary syndrome and Offspring’s Risk of Cardiovascular diseases in Childhood and Young Adulthood - Fen Yang; Ziliang Wang; Henrik Toft Sørensen; Imre Janszky; Mika Gissler; Wei Yuan; Maohua Miao; Nathalie Roos; Anna-Karin Wikström; Jiong Li; Krisztina D. László (Nature Communications)
Abstract Children born to mothers with polycystic ovary syndrome have a higher prevalence of cardiovascular risk factors and of subclinical cardiovascular disease, but the association between maternal polycystic ovary syndrome and cardiovascular disease in offspring is unclear. We conduct a register-based cohort study of 6 839 703 live singleton births from Denmark (1973–2016) and Sweden (1973–2014) and follow them for up to 48 years. Using Cox regression models, we find that offspring of mothers with polycystic ovary syndrome have a higher risk of overall cardiovascular diseases and of its specific subtypes, independently of comorbidities related to polycystic ovary syndrome. Cousin analyzes suggest that familial confounding does not explain our results. If our findings are replicated by future studies, children of women with polycystic ovary syndrome may benefit from early cardiovascular prevention efforts.